Eurocodes for bridge design versus mechanics - Sławomir Karaś; Wioleta Czubacka (Budownictwo i Architektura, 2013)
Regulations on which designers base their process of designing of any engineer structures should  include and combine mechanics, loads and dimensioning. It is not always the case as far as eurocodes are concerned. Ambiguities appear everywhere, which  sometimes leads to  incorrect understanding of a norm. The authors meticulously analysed  basic mechanical terms. Their digressions began with  the concepts of strain and deformation that have discrepant definitions in sources from other countries. The next part of article discusses the concept of „shear lag”. It is treated as an elementary concept in the eurocodes, although is has not been defined yet. Other sources define it as cooperating width and shear strain in the beam flanges or as stretching. Polish translation mentions the effect of „wide stripes”. The authors focused also on dynamics – especially while discussing first natural frequencies denoted as “n0”. They scrutinised  the norm EN 1991-2 in which dynamic problems of bridges are understood as effects of service load when the  environmental impact is not included. As always, in a situation when there is a doubt, it is possible apply the to accurate mechanics rules. To sum up, Polish versions of bridge eurocodes should be corrected to be unambiguous and useful in a design.